Analisis Usaha Unit Pengolahan Padi Pada Badan Usaha Milik Desa Harapan Makmur Desa Tebing Tinggi - Pratiwi, Ciptati Nugraha; Ahmad Rifai; Deby Kurnia (Universitas Garut, 2025)
The rice processing business at BUMDes Harapan Makmur operates more actively during the harvest season, depending on the size of the rice harvest in Tebing Tinggi Village. The purpose of this research is to identify rice processing business activities, analyze the financial feasibility of the Heler Unit Business, and analyze the marketing results of the Perdagangan Beras Unit Business. This research method is a case study. Data analysis uses descriptive analysis, financial feasibility analysis, and marketing analysis. The results of this research include the Heler Unit's business activities, namely preparation for filling diesel fuel and checking oil, traveling around, and grinding grain, while the Perdagangan Beras Unit Business activities include drying, milling, packaging and selling. Heler Unit Business at SOCC levels of 6% and 12% are feasible. Marketing analysis was carried out on the purchase of rice and grain with Sokan and PB42 rice varieties, the most efficient marketing channel was marketing channel I for Sokan variety rice at 8%. The Perdagangan Beras Unit Business purchased rice from farmers and marketed it directly to consumers.